Cross-brain neurofeedback: scientific concept and experimental platform. - Lian Duan; Wei-Jie Liu; Rui-Na Dai; Rui Li; Chun-Ming Lu; Yu-Xia Huang; Chao-Zhe Zhu (PLoS ONE, 2013)
The present study described a new type of multi-person neurofeedback with the neural synchronization between two participants as the direct regulating target, termed as "cross-brain neurofeedback." As a first step to implement this concept, an experimental platform was built on the basis of functional near-infrared spectroscopy, and was validated with a two-person neurofeedback experiment. This novel concept as well as the experimental platform established a framework for investigation of the relationship between multiple participants' cross-brain neural synchronization and their social behaviors, which could provide new insight into the neural substrate of human social interactions.